PEMANTAUAN CUACA LOKAL DENGAN SISTEM PENDETEKSI CURAH HUJAN BERBASIS IoT - rahmi hidayati (Djtechno: Jurnal Teknologi Informasi, 2024)
Local weather is a weather condition such as rain, temperature, and humidity that occurs in a certain area. The presence of local weather that occurs unevenly can affect daily activities. There are many weather information providers, but the data presented usually covers a large area so that there can be differences in weather readings in local areas. To address this problem, a system was developed to monitor local weather with an IoT-based rainfall detection system. The purpose of this study is that users can see weather conditions through the website. The website developed can display weather data from each location. The results of the rain sensor test can work well, the rainfall sensor can measure rain intensity and the BME280 sensor for air temperature shows an average error difference of 0.21℃ and an average relative error of 0.74%. Meanwhile, the results of the air humidity test show an average error difference of 0.83°C and an average relative error of 1.31%.